Penerapan Kinerja Filter Rule dengan Metode Raw dan Layer 7 Protocol di Router Mikrotik - Cindy Novi Syahputri; Chintya Anggraini; Hafiz Fawi Anugerah; Ilka Zufria; Muhammad Iqbal Nahwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aims to improve the security and efficiency of network use in government environments, especially in relation to access to social media sites. This research also aims to implement a healthy internet and avoid the negative impacts that come from pornographic websites. The research method used in this research is state general problem, conduct literatur research, desain methodology, implementation,analyze data, and report result. The results of this research show that the implementation of Filter Rule Performance using the Raw Method and Layer 7 Protocol on the Mikrotik Router at the Communications and Information Service of North Sumatera Office has been successful. Filter Rules with the Raw method are used to process packets before Connection Tracking is carried out, so that they can reduce the load on the CPU. Meanwhile, Layer 7 Protocol is used to perform filtering based on the application protocol used in data packets. However, using the L7 Filter Rule also has a weakness, namely that it can consume Router resources if used for Filtering all types of Traffic.Keywords: Filter Rule, Raw Method, Layer 7 Protocol, Router Mikrotik